Personality traits and impulsivity in association with obesity among the students of teachers training colleges - Nor Zam Azihan, Bin Mohd Hassan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Obesity has recently become important to the world of medicine and also public health due to its rapdly increased prevalence both in the developed and developing country. The impulsivity and personality traits have been studied in the past and significantly related to overweight and obesity. Therefore, a cross-sectional study was conducted to determine if personality traits and impulsive behaviours were significantly associated with overweight and obesity among teachers training students.